2018
DOI: 10.1242/bio.036301
|View full text |Cite
|
Sign up to set email alerts
|

It works! Lumpfish can significantly lower sea lice infestation in large-scale salmon farming

Abstract: To assess the efficacy of lumpfish grazing on attached sea lice on Atlantic salmon, six large-scale sea cages, (130 m circumference, 37,688 m3 volume) each stocked with approximately 200,000 salmon 0+ smolts, were stocked with a 4, 6 and 8% density (8000, 12,000 and 16,000, respectively) of lumpfish. The sea cages without lumpfish acted as controls. Sea lice infestation levels on the salmon were monitored weekly and bi-weekly from 6 October to 17 May the subsequent year. Mortality of the lumpfish rose with dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 34 publications
0
54
0
Order By: Relevance
“…Cleaner fish therefore seems to have a different effect on the three lice stages. In an earlier study, lumpfish have been shown to prefer the larger adult female lice (Imsland et al, ). From survival analysis 1, we saw that cleaner fish of 4% or more had a delaying effect on the time before 0.1 adult female was reached.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Cleaner fish therefore seems to have a different effect on the three lice stages. In an earlier study, lumpfish have been shown to prefer the larger adult female lice (Imsland et al, ). From survival analysis 1, we saw that cleaner fish of 4% or more had a delaying effect on the time before 0.1 adult female was reached.…”
Section: Discussionmentioning
confidence: 91%
“…Cleaner fish therefore seems to have a different effect on the three lice stages. In an earlier study, lumpfish have been shown to prefer the larger adult female lice (Imsland et al, 2018).…”
Section: Salmon Lice and Precautionary Actionsmentioning
confidence: 83%
“…Although efficacious, these methods involve stressful handling and have welfare issues for the fish. Many salmon producers are also cultivating various species of cleaner fish (family Labridae and lumpsuckers Cyclopterus lumpus) together with the salmon [13,14]. The sole purpose of these fish is to feed on salmon lice.…”
mentioning
confidence: 99%
“…Lumpfish are a more recent addition, with the first studies to provide evidence for their efficacy at small and large commercial scale conducted in the last 5 yr, (e.g. Imsland et al 2014aImsland et al ,b, 2015Imsland et al , 2016Imsland et al , 2018. Wrasse are widely used in spring and summer but become inactive at temperatures below 6°C (Imsland et al 2014a, Powell et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Cleaner fish are less expensive and less stressful to salmon than chemotherapeutants (Groner et al 2013, Powell et al 2018 and are generally more acceptable to the public than chemotherapeutant use (Imsland et al 2018). All cleaner fish species used in salmon aquaculture are opportunistic cleaners, unlike 'true' cleaner fishes that have dedicated symbiotic relationships with 'client' fishes (Vaughan et al 2017).…”
Section: Introductionmentioning
confidence: 99%